Regression test optimization and automation in Agile framework: A Review (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Regression testing is a well-established practice in software development and has shown itself to be one of the best ways to test the software before its release. The modified code and some existing code affected should be re-tested during regression testing. This often takes time and becomes painful. Therefore, test automation is increasingly required and important in software engineering to carry out the regression test.It is very obvious that nowadays, many companies invest in automated testing tools to prevent defects while developing. Agile methodologies are one of the automated regression testing tools available. The major advantages of agile software development are delivery and change in high-quality software in shorter intervals. Test strategies are well established for conventional process models, but these strategies are not directly applicable without changes or changes to agile tests. Agile methodologies although useful in automation regression testing,have seen some challenges for regression testing. This paper presents detailed examinations and research evidence using agile methods and test automation. It will also address optimization techniques in agile methodologies and challenges faced in agile.